Recent progress in understanding pediatric pulmonary hypertension - Abman, Steven H. (2011)
PURPOSE OF REVIEW: Pulmonary artery hypertension (PAH) in children contributes significantly to morbidity and mortality in diverse pediatric cardiac, lung, hematologic and other diseases. Advances in pulmonary vascular biology over the past few decades have significantly expanded therapeutic strategies; however, many unique issues persist regarding our understanding of pediatric PAH. RECENT FINDINGS: Recent studies of pediatric PAH include those that highlight gaps in our understanding of pediatric diseases associated with PAH from those of adult onset, emphasizing the strong need for specific studies regarding unique aspects of the pathogenesis and treatment of children with PAH. Registries have begun to provide new data showing differences in physiology, course, and genetics between adult and pediatric forms of PAH. Unfortunately, therapeutic strategies in pediatric pulmonary hypertension are often limited to small observational studies in children and are dependent on results from larger adult studies. In addition, clinical endpoints for studies and care remain poorly defined in infants and children. SUMMARY: Despite many advances, long-term outcomes for children with PAH remain guarded and substantial challenges persist, especially with regard to understanding mechanisms and approach to severe PAH. Future studies are needed to develop novel biomarkers, clinical endpoints and interventions for young children with diverse causes of PAH.